The Untold Story of Inuit Printed Fabrics from Kinngait Studios, Kinngait (Cape Dorset), Nunavut, Canada - Shaughnessy, Roxane; Richard, Anna (DigitalCommons@University of Nebraska - Lincoln, 2018)
The Textile Museum of Canada holds a collection of close to 200 printed fabrics designed by Inuit artists at Kinngait Studios in Kinngait (Cape Dorset), Nunavut, Canada in the 1950s and 1960s. The pieces are owned by the West Baffin Eskimo Co-operative (WBEC) and are on longterm loan to the Museum. Building on centuries-old Inuit graphic traditions, printmaking was introduced in Kinngait in 1957 as part of a larger initiative to encourage handicraft production for sale in the Canadian south. By the 1960s, the studio had a number of Inuit artists who contributed to the Kinngait Studios’ print program which included a commercial hand-printed fabric enterprise. A selection of these fabrics exhibited at Expo 67 (The 1967 International and Universal Exposition) in Montreal drew substantial interest but, ultimately, manufacturing textiles in the North proved too expensive and found only a limited market, and this enterprise was abandoned. Based on the research of this unique collection, this paper will discuss the role of experiments in printed fabrics in the development of printed graphic arts, the history and evolution of production and the significance of this short-lived fabric industry in the context of Inuit printmaking. It will consider the broader theme of the relationship between the Inuit and their environment as expressed though cloth as well as the impact of cross-cultural contact on the evolution of Inuit art practices, including the influences of European and Japanese print traditions on Inuit printmaking and the role of the southern Canadian market on design and production decisions. The relationship between fabric and printed designs by well-known Inuit graphic artists will be traced. Today, Kinngait Studios’ print industries continue to offer an artistic and culturally affirming means of recording oral histories, myths and legends of the Inuit, and the place of the printed fabrics in this creative venture will be revealed.